Analisis Kejadian Banjir ROB di Provinsi Bengkulu Periode 2022-2024 - Lisa Asyifa Agustina; Ashar Muda Lubis; Widodo Setiyo Pranowo (Jurnal Kelautan Tropis, 2025)
Bengkulu Province is one of the coastal areas prone to tidal flooding due to a combination of various oceanographic and meteorological factors such as tides, wind speed, rainfall, and sea wave height. This study aims to analyze the dominant factors causing tidal floods in Bengkulu Province during the period 2022-2024. Data on tidal flood events were obtained from BPBD and BPS reports of Bengkulu Province, as well as mass media sources. The analysis was conducted using wind data from the European Center for Medium Weather Forecast (ECMWF), rainfall data from the Meteorology, Climatology and Geophysics Agency (BMKG), and tidal prediction data from the Geospatial Information Agency (BIG). The results show that during the west season, tidal floods are triggered by strong westerly winds due to the West Monsoon, full tides, and moderate to high rainfall, as in the events of February 4-6, 2022 and January 26-27, 2023. During the east monsoon, tidal floods are caused by steady southeast winds and high tides due to the East Monsoon, despite low rainfall, as in the events of July 30, 2023 and August 3-5, 2023. In the transitional season, tidal floods tend to be influenced by a combination of full tides, moderate winds and light to moderate rainfall, such as on May 14-15, 2022 and October 16-17, 2024. Factors such as tropical cyclone activity and the Indian Ocean Dipole (IOD) also contribute significantly to the increased risk of tidal flooding, particularly strengthening winds and increasing rainfall in certain seasons.